Effects of tumor necrosis factor-alpha inhibitors on lipid profiles in patients with psoriasis: a systematic review and meta-analysis - Su, Liang; Xu, Chunyan; Huang, Hong; Zhang, Peilian; Wang, Jinrong; Ouyang, Xiaoyong; Yang, Xuesong; Ye, Jianzhou (Frontiers in Immunology, 2024)
There is no consensus on the effect of tumor necrosis factor-alpha (TNF-alpha) inhibitors on lipid profiles in patients with psoriasis. This study aimed to investigate the effects of TNF-alpha inhibitors on lipid profiles (triglycerides, total cholesterol, low-density lipoprotein, or high-density lipoprotein) in patients with psoriasis. We searched PubMed, Embase, and Cochrane Library databases for articles published before October 17, 2023. Four TNF-alpha inhibitors (infliximab, etanercept, adalimumab, and certolizumab) were included in our study. A total of twenty trials were included. Overall results revealed that TNF-alpha inhibitors elevated high-density lipoprotein levels in patients with psoriasis (WMD = 2.31; 95% CI: 0.96, 3.67; P = 0.001), which was supported by the results of sensitivity analyses excluding the effect of lipidlowering drugs. Subgroup analyses indicated that high-density lipoprotein levels were significantly increased in the less than or equal to 3 months group (WMD = 2.88; 95% CI: 1.37, 4.4; P < 0.001), the etanercept group (WMD = 3.4; 95% CI = 1.71, 5.09, P < 0.001), and the psoriasis group (WMD = 2.52; 95% CI = 0.57, 4.48, P = 0.011). Triglyceride levels were significantly increased in the 3 to 6-month group (WMD = 4.98; 95% CI = 1.97, 7.99, P = 0.001) and significantly decreased in the 6-month and older group (WMD = -19.84; 95% CI = -23.97, -15.7, P < 0.001). Additionally, Triglyceride levels were significantly increased in the psoriasis group (WMD = 5.22; 95% CI = 2.23, 8.21, P = 0.001). Our results revealed that TNF-alpha inhibitors might temporarily increase high-density lipoprotein levels in patients with psoriasis. However, changes in triglycerides were not consistent among the different durations of treatment, with significant increases after 3 to 6 months of treatment. Future prospective trials with long-term follow-up contribute to confirming and extending our findings.